Skrining aktifitas antibakteri dari ekstrak Sisik Naga (Pyyrosia piloselloides (L) M.G.Price) - desi sagita; Muhammad Nurul Ichwani; Linuria Linuria (Riset Informasi Kesehatan, 2017)
Abstract Background : Sisik naga herbs (Pyyrosiapiloselloides (L) M.G. Price) is an epiphyte plants with compounds of flavonoids and tannins. The compound provides antibacterial potency. This plant is effective for wounds, canker sores, constipation and dysentery. The antibacterial activity of the plant is potentially for development of medicinal plant compounds. The extraction process by maceration for 3 days with three repetitions. From 1 kg of weight of Sisik naga obtained 4.95% extract. Antibacterial test using the dilution methods. The results showed the Sisik naga herbs provide antibacterial activity with MIC 256 Î¼g/mL and MBC 512 Î¼g/mL against bacteria Pseudomonas aeruginosa and Staphylococcus aureus. As a positive control used a solution of chloramphenicol.(Objective) This research is aimed to knowing the antibacterial activity of ethanol extracts from Sisik naga hersb. Method : The extraction process by maceration for 3 days with three repetitions with ethanol. Antibacterial avtivity tes by dilution methods. Results :. From 1 kg of Sisik naga obtained 4.95% extract.. The results showed the Sisik naga herbs provide antibacterial activity with MIC 256 Î¼g/mL and MBC 512 Î¼g/mL against bacteria Pseudomonas aeruginosa and Staphylococcus aureus. As a positive control used a solution of chloramphenicol Conclusion : herb Sisik naga extracts showed antibacterial activity to Pseudomonas aeruginosae and Staphylococcus aureus Key words: antibacterial, sisik naga , dilution methods